Chronic exposure to liquid sucrose and dry sucrose diet have differential effects on peripheral taste responses in female rats. (1st February 2020) - McCluskey, Lynnette Phillips; He, Lianying; Dong, Guankuo; Harris, Ruth
Abstract: Sugar-sweetened beverages are the major source of added calories in the Western diet and their prevalence is associated with obesity and metabolic disruption. Despite the critical role of the taste system in determining food selection and consumption, the effects of chronic sucrose consumption on the peripheral taste system in mammals have received limited attention. We offered female Sprague Dawley rats free access to water and one of three diets for up to 40 days: (1) sucrose-free chow or "NS" diet; (2) a high-sucrose dry diet or "HS"; or (3) 30% sucrose solution and the NS diet, designated "LiqS" diet. Sucrose consumption by LiqS rats gradually increased and by day 14 was equal to that of HS rats. Food intake decreased in LiqS rats, but their energy intake remained higher than for NS or HS rats. There was no significant difference in weight gain of the groups during the study. Recordings from the chorda tympani nerve (CT), which innervates taste buds on the anterior tongue, revealed decreased responses to 1 M sucrose in both LiqS and HS rats and to acesulfame K and salt tastants in LiqS rats after 40 days on diet. Umami, bitter, and acid response magnitudes were unchanged in both groups. These results demonstrate that chronic sucrose exposure inhibits taste responses to higher concentrations of sweet stimuli. More surprisingly, CT responses to NaCl and 0.5M NaAc were significantly reduced in rats on the LiqS diet. Thus, the physical form of the diet influences taste responsiveness to salt and sweet taste function. These data suggest that taste buds are previously unappreciated targets of chronic sucrose consumption.